Clinical implications for pro-GRP in small cell lung cancer. A single center experience. Issue 1 (January 2018) - Cavalieri, Stefano; Morelli, Daniele; Martinetti, Antonia; Galli, Giulia; Nichetti, Federico; de Braud, Filippo; Platania, Marco
Background: Recently, pro-gastrin-releasing peptide (pro-GRP) became available as an alternative sensitive, specific and reliable tumor marker for patients with small cell lung cancer (SCLC), both in limited (LD) and diffuse disease (DD). Methods: We retrospectively analyzed pro-GRP, neuron-specific enolase (NSE) and CEA in patients with SCLC and non-small cell lung cancer (NSCLC). Serum pro-GRP level was measured with electrochemiluminescence at our laboratory (cutoff 77.8 pg/mL). Continuous variables were analyzed with the Mann-Whitney test, contingency data with Fisher's exact test. Receiver operator characteristic (ROC) curve analysis was performed to identify threshold values to set the highest sensitivity (Sn) and specificity (Sp) values. Results: A total of 65 patients were studied (49 men, median age 67 years, range 27-79). Thirty-seven patients had SCLC (29 DD, 8 LD) and 28 advanced NSCLC. Median pro-GRP level was 919 pg/mL (range 22-147, 350) in SCLC and 32 pg/mL (range 10-119.2) in NSCLC (p<0.0001). NSE was 4.38-fold higher in SCLC patients (p = 0.0005); CEA did not reveal significant differences between groups. Pro-GRP Sn and Sp were 86.4% and 96.4%, respectively. With ROC curve analysis, a cutoff value of 329.3 pg/mL showed a Sn of 75.8% and Sp of 87.5% in discriminating DD from LD. Pro-GRP was not influenced by either liver metastases or renal impairment. Conclusions: Pro-GRP is sensitive for SCLC diagnosis. Since high marker levels are related to high disease burden, pro-GRP may have a negative prognostic significance. Follow-up studies are required to define its role in clinical practice in monitoring responses to treatment and early relapses.